A Young Opponent in the Period of Abdulhamid II: The Exile of Ahmed Mikdâd Efendi - Fi̇dan, Erhan Salih (Kastamonu Üniversitesi, 2020)
Ahmed Mikdâd Efendi is a mudarris, teacher, poet and author who lived between 1872-1939. Ahmed Mikdâd Efendi, who was born in Sivas/Divrigi in march 1872, came to Istanbul with his parents when he was eight years old and continued his education here. He had a quality education at Fatih Madrasahs. When he was twenty-seven years old, he continued education in madrasah, he was exiled due to his opposition discourses to Abulhamid II and the period of autocracy. As a result of this exile, he started to work as a teacher and later as a mudarris in Erzincan. Ahmed Mikdâd Efendi, who remained away from written and verbal opposition in Erzincan, after the declaration of the second constitutionalism, went to Istanbul and printed the books he wrote; he published the articles in various journals. In these works, he continued opposition to the period of autocracy. In this article, the exile of Ahmed Mikdâd Efendi from Istanbul; the reasons for the exile and the consequences of his exile are discussed. These issues were investigated in the light of the archive documents and the information provided by Ahmed Mikdâd Efendi’s son. The criticisms he expressed in the works he wrote after the declaration of the second constitutionalism were also mentioned in this study.

Ahmed Mikdâd Efendi, 1872-1939 yılları arasında yaşamış bir müderris, muallim, şair ve müelliftir. 1872 Mart ayında Sivas/Divriği’de doğan Ahmed Mikdâd Efendi, sekiz yaşında iken anne ve babasıyla İstanbul’a gelmiş ve tahsiline burada devam etmiştir. Fatih Medreseleri’nde ciddî bir eğitim görmüştür. Yirmi yedi yaşında iken medresede eğitime devam ettiği dönemde Sultan II. Abdülhamid ve devr-i istibdât karşıtı beyânâtı sebebiyle sürgün edilmiştir. Bu sürgün neticesinde Erzincan’da muallimlik ve daha sonraları müderrislik vazifesine başlamıştır. II. Meşrûtiyet’e kadar Erzincan’da yazılı ve sözlü muhalefetten uzak kalan Ahmed Mikdâd Efendi, II. Meşrûtiyet’in ilanından sonra İstanbul’a giderek yazdığı kitapları bastırmış; çeşitli dergilerde makaleler neşretmiştir. Bu eserlerinde istibdât devri muhalefetine devam etmiştir. Bu makalede, Ahmed Mikdâd Efendi’nin İstanbul’dan sürgün ediliş süreci; sürgün edilme sebepleri ve bu sürgünün neticeleri ele alınmıştır. Ele alınan bu hususlar, arşiv belgeleri ve Ahmed Mikdâd Efendi’nin oğlunun verdiği bilgiler ışığında tetkik edilmiştir. II. Meşrûtiyet sonrasında kaleme aldığı yazı ve eserlerindeki eleştirileri de bu çalışmada zikredilmiştir.
Keywords: Türk-İslam Edebiyatı; Ahmed Mikdâd Efendi; II. Abdülhamid; Sürgün; İstibdât Devri; Din Araştırmaları; Turkish-Islamic Literature; Ahmed Mikdâd Efendi; Abdulhamid II; Exile; Period of Autocracy; Religious Studies; 4. Education; 16. Peace & justice